Development of Ready-Mix Potting Soil Products and Elephant Dung Fertilizer for Income-Generating Activities of the Phawa Sub-District Agroforestry Network, Chanthaburi Province - Khermkhun, Jeeranun; Kullachai, Peerachai; Panrosthip Thunmathiwat, Duangkamol; Kullachai, Kallayanee; Poythaisong, Pakapon (Area Based Development Research Journal, 2022)
Phawa Subdistrict Agroforestry Network, Kaeng Hang Maeo district, Chanthaburi Province required more revenue-generating activities and new members. This research, therefore, aims to develop income-generating activities that will attract new members to join the group. The emphasis is on ecologically-based economic development on local capital, resources, and knowledge in the community. The processes are as follows: 1) joint development of product quality, 2) joint development of product image, 3) transferring knowledge and training, and 4) developing online marketing skills and building a network by selling ready-mix potting soil products and elephant dung fertilizer at Farm Chao Khun by KMITL, community shops, and online channels. As a result, the community generates 6,500 Baht of extra income and arranges training courses to transfer knowledge to youth and stimulate interest and participation. Finally, the Patcharasuthakhachanurak project has supported the product and promoted ready-mix potting soil products and elephant dung fertilizer as a conservation product.